Atherosclerosis in Children and Adolescents - Fauzi Mahfuzh; Sudigdo Sastroasmoro; Sukman Tulus Putra (Indonesian Pediatric Society, 1997)
Being an old disease, atherosclerosis is now considered as die leading cause of death in industrial countries and in some developing countries, and a steady increase of the proportion of death from cardiovascular disease is seen every' where. In the USA death from cardiovascular disease rose from 14% of all death in 1937 to 54% in 1968. Although clinical manifestations of atherosclerosis usually occur at adult age, its pathogenesis has been shown to start at early life. Fatty streak has been shown in not less than 5% of apparently normal children below 1 year of age. We discuss in considerable details the risk factors for atherosclerosis and the role of pediatneian in controlling this disease. Algorithm of screening and diagnosis of high risk children and adolescents for atherosclerosis, as well as the basis of its management are til so discussed. Step care dietetic program is very important, although use of certain drugs is warranted in selected cases.